Public Schooling, Social Capital and Growth - Mark Gradstein; Moshe Justman (University of Copenhagen, Economic Policy Research Unit (EPRU), 1999)
We consider the contribution of public education to growth through its role in building social capitalinstilling common values and norms that lower economic transaction costs and reduce social tensions between different population groups. This is modeled in the context of a political economy framework that focuses on the role of public education in reducing redistributive rent-seeking. Our analysis shows that the social compromises needed to mobilize popular support for public education are more difficult to achieve the deeper are the cultural divisions in society; and that a uniform public school system, when adopted, promotes stronger growth than would a private system.
Keywords: 330